11+4*x/(-5)=2/3

Simple and best practice solution for 11+4*x/(-5)=2/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11+4*x/(-5)=2/3 equation:


11+4*x/(-5)=2/3

We simplify the equation to the form, which is simple to understand
11+4*x/(-5)=2/3

Simplifying:
11+4x/(-5)=2/3

Simplifying:
11+4x/(-5)=0.666666666667

Reorder the terms in parentheses
11+(-0.8x)=0.666666666667

Remove unnecessary parentheses
+11-0.8x=0.666666666667

We move all terms containing x to the left and all other terms to the right.
-0.8x=0.666666666667-11

We simplify left and right side of the equation.
-0.8x=-10.3333333333

We divide both sides of the equation by -0.8 to get x.
x=12.9166666667

See similar equations:

| 9c^2+16c-4=0 | | 64/(9*3-19)= | | 2x+48=-77+3x | | (4+2n^3)+(5n+2)=0 | | 3x^0=0 | | 2x+48=77-3x | | 2x+48=77+3x | | (3+n)6=36 | | 5b^2+7b+6=0 | | 5b^2+7b+6=o | | 3x+2+x+3=x+3 | | 2x+8+3X+14=7X-2 | | 6x=2x | | (8u^2)-47u-6=0 | | 25-(11*2)+6= | | 6x-8=62 | | 3x+2+2x+1=x+3 | | x+(-4+2x)=4 | | 2x+48=168 | | 2x+48=-7x+168 | | -4a+7=a | | -8=(1/9)*(-9)*t+27 | | 9(2x+3)=-36-27(x+2) | | -5/8+m=1/3 | | -4x-7y=20 | | 8/5=2m+3/8 | | 48-2x=168+7x | | 48+2x=168+7x | | -15+7c+1=3-8c | | (3x+7)-3(2x-1)=-2 | | 48+2x=7x+168 | | -1=b/4-7 |

Equations solver categories